Ultra-Wideband Patch Antenna Array With an Inclined Proximity Coupled Feed for Small Unmanned Aircraft RADAR Applications - Abhishek K. Awasthi (IEEE, 2021)
This paper the design of a lightweight and compact patch antenna array with an inclined proximity coupled feed. The antenna array is designed for operation on a small unmanned aircraft system (sUAS) with an ultra-wideband (UWB) radar for remote sensing of soil moisture and snow. To achieve UWB impedance matching, the design utilizes an inclined wide feed and inter-element coupling. A 3-D printed base (polylactic acid) is used to support the feed structure. The antenna array operates over a 2.5 GHz – 4.5 GHz frequency (57.2% bandwidth) range, and its weight is 112 grams. A prototype $2×4$ element array is fabricated and tested. The antenna array has an 88.2% average radiation efficiency and a 13.2 dBi average realized gain over the desired frequency band with broadside and stable radiation pattern.